Speech-tones and melodic expressions: A comparative study of “Jasmine Flower" folksong variants from Jiangsu and Beijing - Liang Tao; Jacqueline Pugh-Kitingan; Lee Chie Tsang Isaiah (Penerbit Universiti Malaysia Sabah, 2024)
The traditional Chinese folksong "Jasmine Flower" is a culturally rich artifact, that has many variants across mainland China. Its variations in melody, rhythm, and lyrics, reflect diverse regional cultures. This study focuses on two representative regional variants—the Jiangsu and Beijing versions—delving into a comprehensive exploration of poetic verses and melodies between the two different regional dialects. Special attention is paid to examining the intricate relationship between dialectal speech-tones and the folksong melodies, highlighting how cultural diversity shapes this musical connection. Data collection for this study involved recording recitations of the poetic verse of each of these two regional variants of the “Jasmine Flower” folksong, each accompanied by its corresponding melodic transcription. The linguistic software PRAAT was utilized for analyzing these dialect recitations, allowing for a comparison between speech-tones and folksong melody, representing a pioneering use of contemporary linguistic approaches in studying the “Jasmine Flower” folksong. The evaluation framework, centered around three comparative criteria between speech-tones and melodic structures: similar motion, oblique motion, and contrary motion, providing a comprehensive lens for analysis. The study's findings reaffirm the significant influence of language and musical traditions on the construction of regional melodies in the various versions of the folksong. Through a superimposed contrastive analysis of the two regional variants, this study elucidates how these versions maintain common characteristics across different levels of melody and poetic structures. This study, thus, not only enriches understanding of the musical heritage embodied in "Jasmine Flower" but also underscores the broader interplay between language and music within regional folk traditions.